Predictors of self-care behaviors in hypertensive patients based on the protection motivation theory - Masoud Karimi; Laila Ghahremani; Tayebeh Rakhshani; Abdolrahim Asadollahi; Atefeh Mohammadi (BMC, 2024)
Abstract Introduction Globally, hypertension is a significant public health concern and a leading cause of premature death. Since this disease is incurable, it is necessary to promote patients' self-care behaviors to control it. The goal of this research was to identify the elements that influence self-care actions in individuals with hypertension, utilizing the Protection Motivation Theory (PMT) framework. Methods A study was carried out in Omidiyeh, located in southern Iran, using a cross-sectional design, involving 397 adults with hypertension (198 females and 199 males) who were selected from comprehensive health centers using a stratified random sampling technique. Data was gathered through a demographic data collection form and a questionnaire created by the researcher, which was based on the PMT. Data were assessed utilizing SPSS 25 and AMOS 24 software, and various statistical tests including one-way ANOVA, Pearson correlation, multiple regression, independent t-test, and structural equation modeling were conducted. Findings The variables of intrinsic reward (r = 0.182), extrinsic reward (r = 0.288), and response cost (r = 0.126) showed a significant negative correlation with self-care behaviors. On the other hand, perceived susceptibility (r = 0.212), perceived severity (r = 0.110), self-efficacy (r = 0.555), and response efficacy (r = 0.424) demonstrated a significant positive correlation with self-care behaviors. Specifically, self-efficacy and response efficacy were the most powerful predictors of self-care behaviors, respectively. Conclusion The results showed that several factors can forecast self-care behaviors in patients with hypertension. Researchers are recommended to incorporate PMT in educational interventions and concentrate on self-efficacy and response efficacy constructs.